Regional differences in alcohol consumption in Croatia - Benčević, Henrietta (Array, 2009)
Summary: This study aims to estimate regional and gender differences in the prevalence of alcohol consumption in Croatia. It is based on the data obtained from the Croatian Adult Health Survey 2003. The highest prevalence of alcohol consumption in men was reported in Eastern Croatia (14.1%). Men living in the Mountainous region had the lowest prevalence of reported alcohol consumption (8.8%). In contrast to men in the Eastern region, women in the same region reported drinking alcoholic beverages with the lowest prevalence (0.3%). The highest proportion of women who reported drinking alcoholic beverages was recorded the Northern Croatian region (1.5%). Results support the expected gender gap in alcohol consumption and point out strong regional pattern of alcohol consumption. The observed pattern shows that primary prevention and health promotion should be implemented with special concern to regional differences and traditions